Ernst Papanek and Jewish Refugee Children Genocide and Displacement - Jacob, Frank (Genocide and Mass Violence in the Age of Extremes, 2021)
Ernst Papanek (1900-1973) was an Austrian-born Viennese reform pedagogue who realized already in the 1930s that unaccompanied, traumatized young refugees were self-directed. He organized "Kindertransporte" for about 1,600 refugees between 1938 and 1940.